2016
DOI: 10.1097/mcg.0000000000000425
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Angioectasias Are Not Randomly Distributed in the Small Bowel and Most May Be Reached by Push Enteroscopy

Abstract: Push enteroscopy for bleeding angioectasias is effective in many patients. Deep enteroscopy may not benefit most patients as most angioectasias are proximal. Patients with deeper lesions tended to have multiple lesions and rebleeding despite deep enteroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…To the best of our knowledge, this is the first study presenting a large consecutive patient-series, in a clinical practice setting, undergoing VCE with CapsoCam SV. It should be noted however that in patients with positive VCE, 25% of P2 lesions were located in the upper GI tract, whereas the distribution of P2 lesions along the small bowel was similar to that described in previous studies [25,26]. Although it is well known that upper GI lesions may be missed by conventional gastroscopy and identified at the time of VCE, the frequency reported in studies using forward-viewing cameras is lower than that observed in our study (range 4-…”
Section: Discussioncontrasting
confidence: 55%
“…To the best of our knowledge, this is the first study presenting a large consecutive patient-series, in a clinical practice setting, undergoing VCE with CapsoCam SV. It should be noted however that in patients with positive VCE, 25% of P2 lesions were located in the upper GI tract, whereas the distribution of P2 lesions along the small bowel was similar to that described in previous studies [25,26]. Although it is well known that upper GI lesions may be missed by conventional gastroscopy and identified at the time of VCE, the frequency reported in studies using forward-viewing cameras is lower than that observed in our study (range 4-…”
Section: Discussioncontrasting
confidence: 55%
“…Moreover, in this study, vascular lesions were frequently observed in the proximal small bowel even though the retrospective type of study did not allow a comparison of VCE with enteroscopy. However, despite the fact that the reason for this location is unclear, this finding could explain what is reported in the literature, i.e., the good performance of enteroscopy in identifying and, mostly, in treating this type of injury [22,23]. Finally, a recent European study showed that the diagnostic yield of VCE was not adequately effective in the case of small bowel masses when they did not protrude into the lumen [24].…”
Section: Discussionmentioning
confidence: 99%
“…Of these lesions, 67% were in the duodenum and 78% were within the first 25% of small bowel transit, suggesting that the majority of these lesions are within the reach of PE. 18 Thus, PE may be useful when VCE localizes lesions to the proximal small bowel.…”
Section: Push Enteroscopymentioning
confidence: 99%